"A Bold Enterprise": The Ecumenical Review and the Beginnings of the World Council of Churches. Issue 3 (11th November 2018) - Brown, Stephen G.
Abstract: The need for an "authoritative, Christian, ecumenical review" to serve as a platform for the nascent ecumenical movement was one of the elements of the proposals to bring together the movements on Faith and Order and Life and Work to form a single World Council of Churches (WCC). This article traces the main stages in creating such an ecumenical journal from the Oxford and Edinburgh conferences of 1937 to the launch of The Ecumenical Review immediately before the founding assembly of the WCC in Amsterdam in 1948, and the particular role played in this by Willem A. Visser 't Hooft, the WCC's first general secretary.